Marital Status and Its Association with Leading Cardiovascular Risk Factors of Ischemic Heart Disease - Oleg O. Zhurba (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To establish a relationship between marital status and frequency of cardiovascular risk factors: type II diabetes, hypertension, overweight, smoking, and hypodynamia.Materials and methods. The study included patients with coronary artery disease (CAD) who underwent off-pump coronary bypass surgery. The total number of people in the sample was 3674, the mean age of the patients was 60.6 ± 0.8 years. Medical history, case records and results of general clinical and laboratory examinations provided for inpatient treatment became the material for analysis. The study design was based on the patient’s age according to the WHO age classification. The relationship between marital status and leading cardiovascular risk factors was calculated using the odds ratio and relative risk.Results. As a result of studying the relationship between marital status as a leading factor in a person’s social status, it was established that the presence of a partner relationship was associated with a 1.50-fold increased risk of overweight (p = 0.0003, χ2 = 21.59), 1.07-fold increased risk of hypertension (p = 0.005, χ2 = 7.60) and 1.26-fold increased risk of type II diabetes (p = 0.04, χ2 = 4.28). Taking into account the age of the patients, it was found that senile married people had an increased risk of overweight (p = 0.0001, χ2 = 20.51) and elderly patients had an increased risk of hypertension (p = 0.002, χ2 = 9.73). It was found that loneliness in patients with CAD was associated with a 4.97-fold increase in the frequency of obese people (p = 0.08, χ2 = 3.02) and smokers (p = 0.0001, χ2 = 182.60). It was also determined that young single patients were significantly more likely to smoke (p = 0.0001, χ2 = 102.19).Conclusions. As a result of the study, the associations of loneliness with leading cardiovascular factors regarding the risk of developing coronary heart disease were clarified. It was found that single persons, as a group with an unfavorable socio-economic status, had increased cardiovascular risks: obesity (p = 0.08, χ2 = 3.02) and smoking (p = 0.0001, χ2 = 121.16). It was also established that young single patients were significantly more likely to smoke (p = 0.0001, χ2 = 102.19), and elderly family patients had a significantly higher risk of overweight (p = 0.0001, χ2 = 20.51), and hypertension (p = 0.002, χ2 = 9.73).